2020
DOI: 10.37231/jab.2020.11.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Generation and Callus Induction of Dioscorea hispida Dennst by Different Plant Growth Hormones and Basal Media

Abstract: Dioscorea hispida Dennst produces tuber which possess valuable medicinal properties but unsustainable harvesting has led to its reduction. The plant propagates slowly because of its low tuber sprouting rate. In average, Dioscorea hispida Dennst tubers took approximately 60 d to break dormancy and sprout. Hence, callus culture is proposed as a possible efficient type of culture for manipulation of this species.  In the present study, calli were induced from stem segments to evaluate callus culture potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, leading to rapid growth and development which contributed to higher leaf area of leaves (Akwatulira et al, 2011). Mahmod et al (2020) also reported that plant growth regulators application improved callus multiplication and differentiation in the stem culture of ubi gadong. Our study indicated that rooting hormone, rooting medium and their interaction produced significant effects on leaf chlorophyll content of wax apple air layers.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, leading to rapid growth and development which contributed to higher leaf area of leaves (Akwatulira et al, 2011). Mahmod et al (2020) also reported that plant growth regulators application improved callus multiplication and differentiation in the stem culture of ubi gadong. Our study indicated that rooting hormone, rooting medium and their interaction produced significant effects on leaf chlorophyll content of wax apple air layers.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, the rooting media and interaction of rooting media and hormones produced a significant effect on leaf area of rooted wax apple air layers. With root inducing hormone applied with rooting medium produced more roots in cuttings, thus absorbing more nutrients and water, and increased the leaf area stem cuttings (Stancato et al, 2003;Mahmod et al, 2020). The aeration capacity of the rooting media is accountable for improving metabolic activities, enhancing vegetative growth and survivability of air layers (Yeboah et al, 2009).…”
Section: Discussionmentioning
confidence: 99%